Clinical Experience and Management Strategy of Retroperitoneal Tumor With Venous Tumor Thrombus Involvement - Liu, Zhuo; Ge, Liyuan; Liu, Lei; Zhao, Xun; Chen, Kewei; Li, Yuxuan; Aili, Abudureyimujiang; Lu, Min; Pei, Xinlong; Han, Dengyang; Zhang, Shudong; Ma, Lulin (Frontiers in Oncology, 2022)
Background This study aims to report the surgical management, complications, and outcomes for patients with retroperitoneal tumor and venous thrombus. Methods We retrospectively analyzed 19 cases of retroperitoneal tumor with venous tumor thrombus from August 2015 to March 2021. A new tumor thrombus PUTH-RT grading system was proposed on the basis of the characteristics of the surgical techniques. Results Two cases of PUTH-RT-1a, two cases of PUTH-RT-1b, six cases of PUTH-RT-2, six cases of PUTH-RT-3, and three cases of PUTH-RT-4 were included. Surgeries were successfully performed in all 19 patients. Among them, five cases (26.3%) were operated via a completely laparoscopic approach and 13 cases (68.4%) via an open approach. One case (5.3%) was converted from laparoscopic to open approach. Five cases (26.3%) experienced postoperative complications. All patients were followed for a median of 14 months. Cancer-associated death occurred in three cases. Distant metastases occurred in seven cases. Conclusions We propose a new tumor thrombus grading system based on the anatomical characteristics of retroperitoneal tumors with venous tumor thrombus. Retroperitoneal tumor resection and removal of venous tumor thrombi are safe and effective for the treatment of such diseases.